Synthesis of TUDCA from chicken bile: immobilized dual-enzymatic system for producing artificial bear bile substitute - Tang Shijing; Pan Yinping; Yang Qiong; Lou Deshuai; Zhu Liancai; Tan Jun; Liu Shaoyong; Wang Bochu (Microbial Cell Factories)
Abstract Bear bile, a valuable animal-derived medicinal substance primarily composed of tauroursodeoxycholic acid (TUDCA), is widely distributed in the medicinal market across various countries due to its significant therapeutic potential. Given the extreme cruelty involved in bear bile extraction, researchers are focusing on developing synthetic bear bile powder as a more humane alternative. This review presents an industrially practical and environmentally friendly process for producing an artificial substitute for bear bile powder using inexpensive and readily available chicken bile powder through an immobilized 7α-,7β-HSDH dual-enzymatic syste. Current technology has facilitated the industrial production of TUDCA from Tauodeoxycholic acid (TCDCA) using chicken bile powder. The review begins by examining the chemical composition, structure, and properties of bear bile, followed by an outline of the pharmacological mechanisms and manufacturing methods of TUDCA, covering chemical synthesis and biotransformation methods, and a discussion on their respective advantages and disadvantages. Finally, the process of converting chicken bile powder into bear bile powder using an immobilized 7α-Hydroxysteroid Dehydrogenases(7α-HSDH) with 7β- Hydroxysteroid Dehydrogenases (7β-HSDH) dual-enzyme system is thoroughly explained. The main objective of this review is to propose a comprehensive strategy for the complete synthesis of artificial bear bile from chicken bile within a controlled laboratory setting. Graphical Abstract